From Disaster Response to Risk Management Australia's National Drought Policy - Botterill, Linda Courtenay; Wilhite, Donald A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
In 1992 Australia$1 (Bs Commonwealth and State governments announced the introduction of a National Drought Policy adopting an innovative risk management approach, which received broad support from Australia$1 (Bs major political parties and the policy community. This trail-blazing attempt and the experiences with the development and implementation of this policy over the past decade have intrigued the international scientific and policy communities. The present book comprises an academically focused collection of papers, which the Editors hope will provide others moving in a similar direction with the benefit of experience. The work highlights the successes and challenges of a move from disaster to risk management in responding to drought. As such it will be a valuable and useful addition to the international literature on drought preparedness and response.s
Living in the Australian Environment -- Climate and Drought in the Subtropics: The Australian Example -- Indigenous Water Philosophy in an Uncertain Land -- Late Twentieth Century Approaches to Living with Uncertainty: The National Drought Policy -- Managing Risk?: Social Policy Responses in Time of Drought -- Drought, News Media and Policy Debate -- At the Intersection of Science and Politics: Defining Exceptional Drought -- Drought Risk as a Negotiated Construct -- Prospects for Insuring Against Drought in Australia -- Policy for Agricultural Drought in Australia: An Economics Perspective -- Drought Policy and Preparedness: The Australian Experience in an International Context -- Lessons for Australia and Beyond.
Keywords: Environment; Climate change; Environmental management; Water pollution; Environmental economics; Human geography; Environment; Environmental Management; Climate Change Management and Policy; Environmental Economics; Climate Change; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Human Geography; Electronic books